1993
DOI: 10.1111/j.1365-2354.1993.tb00181.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients' perceptions of breast-cancer-related lymphoedema

Abstract: This article describes a study which was designed to explore patients' perceptions of breast-cancer-related arm lymphoedema and the factors that may be associated with these perceptions. The findings of the study suggest that lymphoedema is a unique and complex experience for the patient which influences many spheres of life. Adjustment to the condition is impeded by higher limb volume and facilitated by appropriate treatment to reduce limb volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
5

Year Published

1998
1998
2009
2009

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 3 publications
0
42
0
5
Order By: Relevance
“…28,[37][38][39][40][41][42][43][44] One prospective study concerned the QOL experienced by survivors of breast carcinoma after breast carcinoma treatment. 42 The other studies were retrospective.…”
Section: Methodologic Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…28,[37][38][39][40][41][42][43][44] One prospective study concerned the QOL experienced by survivors of breast carcinoma after breast carcinoma treatment. 42 The other studies were retrospective.…”
Section: Methodologic Problemsmentioning
confidence: 99%
“…Research conducted with patients with SLE and breast carcinoma has indicated that general psychiatric and QOL tools may not be sensitive enough to detect arm problems among women after breast surgery. 40,43,46,47,54 Research results have also suggested that generic 23,43,55 and cancerspecific QOL tools 39,46,56 may not include a sufficient range of items to comprehensively assess the psychological and social sequelae of arm morbidity. Although generic measures allow for cross-disease comparisons, disease-specific measures are more sensitive to individual change.…”
Section: Research Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fica evidente a importância das ações preventivas no controle do linfedema, e autores referindo-se à qualidade de vida de mulheres mastectomizadas, consideram primordiais as orientações e cuidados em relação a essa complicação que se apresenta como uma experiência única e complexa, influenciando nas várias esferas da vida (Woods, 1993;Granda, 1994;Clapis, 1996).…”
unclassified
“…Estudo a respeito da dimensão psicossocial do linfedema pós-tratamento do câncer de mama, explorando as mudanças nas percepções de 40 mulheres, evidenciou que a preocupação com a imagem corporal foi um dos maiores problemas percebidos por elas (Woods, 1993).…”
unclassified